Air torque position damper hysteresis. (March 2020) - Bikić, Siniša; Bukurov, Maša; Radojčin, Milivoj; Pavkov, Ivan; Rackov, Milan
Abstract: The purpose of this paper is to determine the effect of the air torque position (ATP) damper hysteresis on the accuracy of air velocity measurements and the adequacy of the ATP damper mathematical model tested in the present study. A total of three dampers with non-cascading blades were examined: a damper with a single flat blade, a damper with two opposed flat blades, and a damper with two flat blades - one of which is a measuring blade and the other is fixed in the horizontal direction. Furthermore, a total of two damper installation locations in a duct system were examined as well: at the duct exit with a straight duct section preceding the damper and within the duct itself with straight duct sections both preceding and following the damper. The ATP damper hysteresis was found to exert a significant effect on the accuracy of air velocity measurements and the adequacy of the ATP damper mathematical model tested if the ATP damper is more open, i.e. with lower blade angles of attack. Moreover, the ATP damper installed at the duct exit was found to be more susceptible to hysteresis effects than the damper located within the duct. Highlights: ATP damper hysteresis exerts a significant effect if the damper is more open. ATP damper installed at the duct exit was found to be more susceptible to hysteresis. A fixed ATP damper blade in horizontal direction could mitigate effect of hysteresis. The effect of hysteresis could be reduced by fixing blade angle during measurements.